Parameter Genetik Beberapa Genotipe Mutan Padi (Oryza sativa L.) Galur G10 Generasi Kedua Hasil Iradiasi Sinar Gamma 300 Gray: The Genetics Parameter Of Some Rice Mutant Genotype (Oryza sativa L.) Galur G10 As A Second Generation Which Is From 300 Gray Gamma Radiation - Ni Wayan Sri Suliartini; Dea Puspamiya Rahayu; I Gusti Putu Muliarta Aryana (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
This study aims to examine the genetic parameters of the G10 strain of second generation black  rice from gamma ray irradiation dose 300 Gray which includes the value of broad sense heritability, genetic coefficient, phenotype coefficient, and correlation. The study was conducted from May to September 2021 in Nyurlembang Village, Narmada district, West Lombok regency, West Nusa Tenggara. The experiment was conducted using Group random design (rack) in the expansion (augmented design). Comparison varieties used in this study as many as 2 varieties, namely G10 and Situ Patenggang, repeated 3 times and planted as many as 20 plants, comparison plants were taken 6 samples in each replication, while the genotype of mutant plants was repeated once consisting of 24 genotypes, each genotype was planted as many as 10 plants. The experimental results of all characters showed the value of genetic diversity coefficient (KKG) and phenotypic diversity coefficient (KKF) in all characters have a low value criteria except the number of characters containing grain and the number of empty grain. The character of plant height, flowering Age, Total tillering, productive tillering, the number of contained grain, the number of empty grain, the weight of 100 grains, and the weight of grain per clump has a high heritability value in the broadest sense. The value of medium heritability is indicated by the long character of the panicle. Productive saplings have a real positive relationship to the weight of grain per clump.